Use of Qualitative and Quantitative Research Methods in Poverty and Livelihood Study: Sharing of Some Anthropological Experiences from Academic Research in Western Tarai, Nepal - Prasain, JN (Nepalese Journal of Qualitative Research Methods, 2009)
doi: 10.3126/njqrm.v1i0.1970 Keywords: Livelihood study; Poverty; anthropology Nepalese Journal of Qualitative Research Methods Vol.1 2007 pp.21-36